Indications and postoperative outcomes of surgery for laryngotracheal stenosis: A descriptive study. Issue 1 (February 2021) - Mizuno, Kayoko; Kanazawa, Yuji; Takeuchi, Masato; Kishimoto, Yo; Kawakami, Koji; Omori, Koichi
Abstract: Objective: Tracheal reconstruction is a rare surgical procedure and the actual incidence of or indications for this procedure have not been thoroughly elucidated. We performed the nationwide database analysis to clarify the real-world situation of laryngotracheal surgery requiring cervical tracheal reconstruction. Methods: Patients who underwent surgical treatment for laryngotracheal stenosis or defect from 2008 to 2016 were identified from the Diagnosis Procedure Combination inpatient database, collected from 270 acute care hospitals in Japan. Patients were divided into two groups based on presence/absence of malignancy, and T-tube or tracheotomy dependence at 6 months after surgery was compared between the two groups. Results: One hundred and thirty-four patients (75 males) were identified. The median age at surgery was 65.5 years. The most common indication for surgery was malignancy ( n  = 60, 44.8%), followed by iatrogenic ( n  = 25, 18.6%), trauma ( n  = 6, 4.5%), malformation of the larynx and trachea ( n  = 6, 4.5%), and chronic inflammatory disease ( n  = 4, 2.8%). Thyroid cancer was the most common malignancy ( n  = 38). Thirty patients (22.4%) failed to decannulate within 6 months and malignancy was associated with a lower dependence on T-tube or tracheotomy at 6 months after surgery (adjusted odds ratio: 0.25, 95% confidence interval: 0.08–0.79). Conclusion: A Japanese health insurance claims database provided a useful overview of the clinical features and outcomes of patients who underwent cervical tracheal reconstruction surgery for laryngotracheal stenosis or defect.